COMBINING COOPERATIVE LEARNING WITH READING ALOUD BY TEACHERS - Jacobs, George; Hannah, Dan (International Journal of English Studies, 2009)
This article begins with a section that describes cooperative learning and explains eight cooperative learning principles. The second section discusses the interface between cooperative learning and language pedagogy. Next is a section about the why and how of reading aloud by teachers. The heart of the article resides in the last and longest section which describes techniques for integrating cooperative learning with reading aloud by teachers. These techniques include ones that can be used before, while and after the teacher has read aloud to the class.